2020
DOI: 10.1159/000511361
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Alternative Version of the Epworth Sleepiness Scale to Assess Daytime Sleepiness in Adults with Physical or Mental Disabilities

Abstract: <b><i>Introduction:</i></b> Excessive daytime sleepiness (EDS) is a frequent symptom with many possible causes, and many of these can be treated. EDS and its underlying causes have been associated with various negative health consequences. Recognition of EDS is thus an important public health concern. The concept of EDS is, however, not yet well defined, and different measures are used to diagnose EDS. The Epworth Sleepiness Scale (ESS) is the most widely used tool to assess daytime sle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…However, these differences reflect real sociodemographic differences between the 2 populations. 45 When interpreting our results, it should be taken into account that, although the PSQI and the ESS are considered "gold standards," these instruments were not designed for patients with mental disorders 37,38,46 and recent examinations have revealed that the ESS has shortcomings with regard to its psychometric properties. 47 Previous findings that sleep disorders are often underdiagnosed and undertreated in patients with mental illness were confirmed in our study: Up to 89% of our patients reported sleep-related difficulties on the screening questionnaires, strengthening the need for a routine clinical screening instrument that can be easily applied in practical psychiatry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these differences reflect real sociodemographic differences between the 2 populations. 45 When interpreting our results, it should be taken into account that, although the PSQI and the ESS are considered "gold standards," these instruments were not designed for patients with mental disorders 37,38,46 and recent examinations have revealed that the ESS has shortcomings with regard to its psychometric properties. 47 Previous findings that sleep disorders are often underdiagnosed and undertreated in patients with mental illness were confirmed in our study: Up to 89% of our patients reported sleep-related difficulties on the screening questionnaires, strengthening the need for a routine clinical screening instrument that can be easily applied in practical psychiatry.…”
Section: Discussionmentioning
confidence: 99%
“…When interpreting our results, it should be taken into account that, although the PSQI and the ESS are considered “gold standards,” these instruments were not designed for patients with mental disorders37,38,46 and recent examinations have revealed that the ESS has shortcomings with regard to its psychometric properties 47…”
Section: Discussionmentioning
confidence: 99%
“…Hilfreich sind zudem validierte Skalen wie Stop‐Bang oder der Berlin‐Fragebogen 15 . Die Quantifizierung der Tagesschläfrigkeit erfolgt häufig mithilfe der Epworth Sleepiness Scale (ESS) 16 , deren Aussagekraft bei gebrechlichen älteren Menschen jedoch eingeschränkt ist und möglicherweise einer Adaptation bedarf 17 .…”
Section: Klassifikation Der Schlafstörungenunclassified